The Idea of Prostitution. - Jeffreys, Sheila (Spinifex Press, 1997)
Explores the idea of men's entitlement to abuse and profit from the abuse of women in prostitution. This work argues that it is important to recognise men's abuse of women in prostitution as a variety of male sexual violence and a violation of women's human rights.